2017
DOI: 10.1021/acs.energyfuels.6b02942
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Clathrate Hydrate Film Growth Rate by Naturally Occurring Surface Active Components

Abstract: During the production of offshore oil and gas, the cooling of hydrocarbons toward seafloor temperatures enables the formation of gas hydrates, which may restrict fluid flow and ultimately block the flowline. During the formation of a hydrate blockage, a hydrate film may grow between individual particles or between hydrate particles and the pipeline wall, respectively resulting in a higher slurry viscosity or a reduced hydraulic diameter. This hydrate film growth rate has been previously studied as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 39 publications
(84 reference statements)
6
29
0
Order By: Relevance
“…This could be because polycyclic aromatics yield better packing than monocyclic ones at the interface. The lower concentration of methane at the interface in the presence of aromatic compounds could reduce the hydrate growth rate 9 , which is consistent with the experimental data obtained in the presence of asphaltenes and resins 48 . When AAs are present at low surface density, fewer methane molecules are present at the interfaces compared to results obtained when no AAs are present.…”
Section: Number Of N-dodecane Moleculessupporting
confidence: 90%
See 1 more Smart Citation
“…This could be because polycyclic aromatics yield better packing than monocyclic ones at the interface. The lower concentration of methane at the interface in the presence of aromatic compounds could reduce the hydrate growth rate 9 , which is consistent with the experimental data obtained in the presence of asphaltenes and resins 48 . When AAs are present at low surface density, fewer methane molecules are present at the interfaces compared to results obtained when no AAs are present.…”
Section: Number Of N-dodecane Moleculessupporting
confidence: 90%
“…On the contrary, our results show that pyrene induces an effective repulsion between two approaching hydrate substrates even when no AA is present (red solid line). The results are consistent with the suppressed cohesive force between water droplet/hydrate particle and hydrate particle in the presence of asphaltene or resin extracted from crude oils (at least by 2 orders of magnitude compared to the system without asphaltene or resin), which has been suggested to be due to the adsorption of asphaltene and resins on the hydrate-oil interface 48 . A shallow free energy well was observed for this system at ~5 nm.…”
Section: Number Of N-dodecane Moleculessupporting
confidence: 84%
“…In the next subsections, some details are provided to explain these phenomena. Presence of activated carbon particles ↓ ↓ [51] Presence of free resins, biding resins, and residual Asphaltenes NA ↓ [141] where ↑: increase; ↓: decrease; NA: Not Acknowledge.…”
Section: Kinetics Of Cph Formationmentioning
confidence: 99%
“…Li et al [139] Finally, Morrissy et al [141] indicated that free resins (FR), binding resins (BR), and residual asphaltenes (RA) in the crude oil reduce CPH film growth rate with a trend in following order:…”
Section: Other Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation